A Sebaceous Cyst Located in the Maxillary Sinus - Popa, Daniela; Juncar, Raluca Iulia; Precup, Alexandru-Iosif; Juncar, Mihai (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Maxillary sinus cysts are quite common, being most frequently detected on the occasion of radiological investigations. On an OPG (orthopantomogram), these cysts appear as round masses, similar to a dome, in contact with one of the walls or the floor of the maxillary sinus. In this study, authors present the case of a patient with a maxillary cyst involving the maxillary sinus. Removal of the maxillary cyst was performed with the extraction of the causative tooth. Complete removal of the sebaceous cyst is mandatory in order to avoid recurrences and potential infectious complications.